Voices from the other side impressions from some Igorot participants in U.S. cultural exhibitions in the early 1900s - Prill-Brett, June (2009)
In the 1900s Igorots from some parts of the Cordillera, such as Bontoc, Suyoc, and Abra, were recruited to join other Filipinos for the purpose of exhibiting their respective ethnic cultures at the 1904 International Exposition in St. Louis, Missouri (see Afable 1997, 2000; Igorot Village 1904: Philippine Exposition 1904). A grand celebration to mark the centennial of the United States' acquisition of the Louisiana Territory from France, this fair became an occasion for the young imperialist nation to show off its new colonial acquisition-the Philippine Islands. The purpose of the first exhibit of Filipino ethnic groups at the Saint Louis Fair was expressed by Albert Jenks (quoted in Jenks 1950, 203-204) in 1904:

The purpose of the ethnologic exhibit at the Exposition in the States is twofold: first, the American visitor may have an opportunity to understand the different tribes of people in these Islands. There will be representatives from all the various stages of culture, from the least-civilized..., the semi-civilized..., to the civilized and cultured....' They will also be represented as naturally as possible so the Americans at home can get as good an idea of the Philippine people as possible without actually visiting the Islands. The second reason for sending them is so that the Filipinos may have a much better idea of what America really is and what her people are- with the result, it is hoped, that seed sown in the Islands by the visitors to America, when they return to their homes in the Philippines, will result in the fruits of peace, industry, and progress along the lines of American ideals for the Islands.
Keywords: Igorot (Philippine people) -- Exhibitions; Igorot (Philippine people) -- Social life and customs